2015
DOI: 10.1016/j.cattod.2014.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the CeZrNd mixed oxide synthesis method in the catalytic combustion of soot

Abstract: Ce0.64Zr0.27Nd0.09O δ mixed oxides have been prepared by three different methods (nitrates calcination, coprecipitation and microemulsion), characterized by N2 adsortion, XRD, H2-TPR, Raman spectroscopy and XPS, and tested for soot combustion in NOx/O2. The catalyst prepared by microemulsion method is the most active one, which is related to its high surface area (147 m 2 /g) and low crystallite size (6 nm), and the lowest activity was obtained with the catalyst prepared by coprecipitation (74 m 2 /g; 9 nm). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…All the samples present type IV isotherms according to the IUPAC classification, which are characteristic of mesoporous solids. 34,35 It can be seen from Fig. 2 that the isotherms of CZ-600 and its corresponding aged sample tend to feature ink-bottle type pores, whereas CZ/N235-600 and CZ/N235-1000 exhibit cylindrical ink-bottle type pores.…”
Section: Resultsmentioning
confidence: 98%
“…All the samples present type IV isotherms according to the IUPAC classification, which are characteristic of mesoporous solids. 34,35 It can be seen from Fig. 2 that the isotherms of CZ-600 and its corresponding aged sample tend to feature ink-bottle type pores, whereas CZ/N235-600 and CZ/N235-1000 exhibit cylindrical ink-bottle type pores.…”
Section: Resultsmentioning
confidence: 98%
“…2c), relating to the bulk and surface Ce 4+ reduction due to the high mobility of oxygen through the lattice. 31 The mass lost during reduction is due to the oxygen loss from the reduction of Ce 4+ to Ce 3+ . The reduction peak temperature is calculated as the temperature of the peak in the derivative TG curve of weight with temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Ceria-zirconia mixed oxides have gradually replaced pure ceria as oxygen storage materials since 1993, because the incorporation of Zr favours the formation of structural defects, accelerates the diffusion of bulk oxygen, enhances the thermal stability of supports and improves the catalytic activity at metal-support interfacial sites. [2][3][4][5][6][7][8][9][10] As emission regulations are continuously being tightened, the new-generation three-way catalyst requires better thermal stability and higher OSC of the oxygen storage component. A great deal of research effort has shown that the addition of transition metals or rare earth metals (La, Pr and Nd) is beneficial to improve the thermal stability and to increase the OSC of ceria-zirconia solid solution by increasing the oxygen vacancies in the fluorite lattice.…”
Section: Introductionmentioning
confidence: 99%